Eudendrium tottoni Stechow 1932 - OLIVEIRA, OTTO M. P.; MIRANDA, THAÍS P.; ARAUJO, ENILMA M.; AYÓN, PATRICIA; CEDEÑO-POSSO, CRISTINA M.; CEPEDA-MERCADO, AMANCAY A.; CÓRDOVA, PABLO; CUNHA, AMANDA F.; GENZANO, GABRIEL N.; HADDAD, MARIA ANGÉLICA; MIANZAN, HERMES W.; MIGOTTO, ALVARO E.; et al. (Zenodo, 2016)
Eudendrium tottoni Stechow, 1932 Synonyms in the area: Eudendrium antarcticum —Broch 1948; Stepanjants 1979 [polyp]; Eudendrium ramosum —Blanco 1984a, 1994a [non Eudendrium ramosum (Linnaeus, 1758)] [polyp]. Distribution in South America: polyp—Atlantic Ocean, at 54.143°S 36.676°W in Puerto Leith, and at South Georgia Islands (Broch 1948; Stepanjants 1979; Blanco 1984a, 1994a). Habitat: polyp—from intertidal zone to 220m depth (Broch 1948; Stepanjants 1979; Blanco 1994a). Published as part of OLIVEIRA, OTTO M. P., MIRANDA, THAÍS P., ARAUJO, ENILMA M., AYÓN, PATRICIA, CEDEÑO-POSSO, CRISTINA M., CEPEDA-MERCADO, AMANCAY A., CÓRDOVA, PABLO, CUNHA, AMANDA F., GENZANO, GABRIEL N., HADDAD, MARIA ANGÉLICA, MIANZAN, HERMES W., MIGOTTO, ALVARO E., MIRANDA, LUCÍLIA S., MORANDINI, ANDRÉ C., NAGATA, RENATO M., NASCIMENTO, KARINE B., JÚNIOR, MIODELI NOGUEIRA, PALMA, SERGIO, QUIÑONES, JAVIER, RODRIGUEZ, CAROLINA S., SCARABINO, FABRIZIO, SCHIARITI, AGUSTÍN, STAMPAR, SÉRGIO N., TRONOLONE, VALQUÍRIA B. & MARQUES, ANTONIO C., 2016, Census of Cnidaria (Medusozoa) and Ctenophora from South American marine waters, pp. 1-256 in Zootaxa 4194 (1) on page 62, DOI:10.11646/zootaxa.4194.1.1, http://zenodo.org/record/10068449